2020
DOI: 10.36560/131020201115
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and distribution in the space-time of the rain erosivity in Goias and Federal District states

Abstract: The ability of rainfall to promote soil disaggregation and transport depends on its intensity and distribution over time, allowing proper soil and water management practices in order to minimize their effects in and outside food production fields. The objective of this study was to verify the intensity of the spatial and temporal distribution of rainfall erosivity in Goias and Federal District states using historical series of rainfall data available at the National Institute of Meteorology (Inmet) from 1986 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Andrade et al (2020b), found for the region of Formosa (GO) average annual erosivity of 8,041.6 MJ mm ha -1 h -1 year -1 for the EI30 index, being from May to September (mainly from June to August) the period with lower and consequently greater erosive potential. Anjos et al (2020) studying the intensity and space-time distribution of rainfall erosivity in the state of Goiá s and Distrito Federal (Pirenópolis, Goiâ nia, Aragarç as, Jataí , Rio Verde, Formosa, Ipameri, Posse, Goiá s, Itumbiara, Catalã o and Distrito Federal) found an average annual R factor of 8,834 MJ mm ha -1 h -1 year -1 , being classified as strong erosive potential.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Andrade et al (2020b), found for the region of Formosa (GO) average annual erosivity of 8,041.6 MJ mm ha -1 h -1 year -1 for the EI30 index, being from May to September (mainly from June to August) the period with lower and consequently greater erosive potential. Anjos et al (2020) studying the intensity and space-time distribution of rainfall erosivity in the state of Goiá s and Distrito Federal (Pirenópolis, Goiâ nia, Aragarç as, Jataí , Rio Verde, Formosa, Ipameri, Posse, Goiá s, Itumbiara, Catalã o and Distrito Federal) found an average annual R factor of 8,834 MJ mm ha -1 h -1 year -1 , being classified as strong erosive potential.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Some studies have already used estimated databases, obtaining positive results, especially the database known as Xavier and NASA POWER (NASA Prediction of Worldwide Energy Resources) (Dender & Sentelhas, 2018, Casaroli et al, 2019, Anjos et al, 2020a.Xav ier's database is limited to The Brazilian territory and was estimated from 3,625 rainfall stations and 735 weather stations installed on the surface of the territory, with the averages corresponding to high resolution grides (0.5 o × 0.5 o ). Nasa POWER data, on the other hand, is based on solar radiation derived from satellite observations and meteorological data from the Goddard Earth Observing System assimilation model, with 1st × 1st grides, available from 1983 to the present day, for any region of the planet Earth.…”
Section: Introductionmentioning
confidence: 99%